Cognitive Impairments in Occupational Burnout – Error Processing and Its Indices of Reactive and Proactive Control - Golonka, Krystyna; Mojsa-Kaja, Justyna; Gawlowska, Magda; Popiel, Katarzyna (Frontiers in Psychology, 2017)
The presented study refers to cognitive aspects of burnout as the effects of long-term work-related stress. The purpose of the study was to investigate electrophysiological correlates of burnout to explain the mechanisms of the core burnout symptoms: exhaustion and depersonalization/cynicism. The analyzed error-related electrophysiological markers shed light on impaired cognitive mechanisms and the specific changes in information-processing in burnout. In the EEG study design (N=80), two components of error-related potential (ERP), error-related negativity (ERN) and error positivity (Pe), were analyzed. In the non-clinical burnout group (N=40), a significant increase in ERN amplitude and a decrease in Pe amplitude were observed compared to controls (N=40). Enhanced error detection, indexed by increased ERN amplitude, and diminished response monitoring, indexed by decreased Pe amplitude, reveal emerging cognitive problems in the non-clinical burnout group. Cognitive impairments in burnout subjects relate to both reactive and unconscious (ERN) and proactive and conscious (Pe) aspects of error processing. The results indicate a stronger ‘reactive control mode’ that can deplete resources for proactive control and the ability to actively maintain goals. The analysis refers to error processing and specific task demands, thus should not be extended to cognitive processes in general. The characteristics of ERP patterns in burnout resemble psychophysiological indexes of anxiety (increased ERN) and depressive symptoms (decreased Pe), showing to some extent an overlapping effect of burnout and related symptoms and disorders. The results support the scarce existing data on the psychobiological nature of burnout, while extending and specifying its cognitive characteristics.